2022
DOI: 10.3389/fpsyg.2022.1037111
|View full text |Cite
|
Sign up to set email alerts
|

Bifactor exploratory structural equation modeling: A meta-analytic review of model fit

Abstract: Multivariate behavioral research often focuses on latent constructs—such as motivation, self-concept, or wellbeing—that cannot be directly observed. Typically, these latent constructs are measured with items in standardized instruments. To test the factorial structure and multidimensionality of latent constructs in educational and psychological research, Morin et al. (2016a) proposed bifactor exploratory structural equation modeling (B-ESEM). This meta-analytic review (158 studies, k = 308, N = 778,624) aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 183 publications
0
3
0
Order By: Relevance
“…Interestingly, this pattern is reflected in our ESEM models from two to three factors. In particular, CFI and TLI changed from 0.865 to 0.867 to 0.945 and 0.934, respectively; while χ2/df ratio and RMSEA changed from 2.68 to 0.055 to 1.84 and 0.035, respectively [ 79 ]. Regarding newly generated items, saturation per item is recommended to be > 0.5, whereas for existing items, saturation for each item is recommended to be ≥ 0.6 [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this pattern is reflected in our ESEM models from two to three factors. In particular, CFI and TLI changed from 0.865 to 0.867 to 0.945 and 0.934, respectively; while χ2/df ratio and RMSEA changed from 2.68 to 0.055 to 1.84 and 0.035, respectively [ 79 ]. Regarding newly generated items, saturation per item is recommended to be > 0.5, whereas for existing items, saturation for each item is recommended to be ≥ 0.6 [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the CFA results for the female group are considered to be within an acceptable range 47 . This may be attributed to a multitude of factors, such as gender‐specific traits in women, sociocultural influences, and model heterogeneity 48,49 …”
Section: Discussionmentioning
confidence: 99%
“…47 This may be attributed to a multitude of factors, such as genderspecific traits in women, sociocultural influences, and model heterogeneity. 48,49 The present study's innovative contribution is the examination of measurement invariance across different clinical status and genders, which was not mentioned in the previous GTQ. This study found that the configural invariance of the GTQ scale was established in different clinical status (H&N cancer and TMD), which indicated that the scale can effectively capture traits and structures related to trismus regardless of an individual's clinical status.…”
Section: Malementioning
confidence: 99%